2008
DOI: 10.1111/j.1537-2995.2007.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Duffy antigen expression is associated with organ damage in patients with sickle cell disease

Abstract: Duffy genotype may be a potential biomarker for the development of end-organ damage in SCD, particularly kidney dysfunction. The association of both WBC counts and hydroxyurea use with Duffy expression provides another avenue for investigation of the biologic role of this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 49 publications
3
50
1
4
Order By: Relevance
“…The data of Afenyi-Annan et al 92 provide evidence that SCD patients with the Fy(aϪbϪ) phenotype are more susceptible to chronic organ damage and proteinuria than SCD patients of normal Fy phenotype and are consistent with such an hypothesis. Interpretation is likely also influenced by genetic differences of immune response and cytokine genes in African populations compared with other world populations, 93,94 but the genetic backgrounds of SCD patients with normal and Fy(aϪbϪ) phenotype may be sufficiently comparable to allow conclusions regarding alloimmunization and the role of Fy to be drawn.…”
Section: Org Frommentioning
confidence: 70%
“…The data of Afenyi-Annan et al 92 provide evidence that SCD patients with the Fy(aϪbϪ) phenotype are more susceptible to chronic organ damage and proteinuria than SCD patients of normal Fy phenotype and are consistent with such an hypothesis. Interpretation is likely also influenced by genetic differences of immune response and cytokine genes in African populations compared with other world populations, 93,94 but the genetic backgrounds of SCD patients with normal and Fy(aϪbϪ) phenotype may be sufficiently comparable to allow conclusions regarding alloimmunization and the role of Fy to be drawn.…”
Section: Org Frommentioning
confidence: 70%
“…Conflicting results have been reported regarding the clinical relevance of DARC erythroid expression in the pathophysiology of SCA (15,30,32,33); Schnog et al (32), and more recently Nebor et al (15) failed to detect any association between DARC erythroid expression and the clinical severity of SCA. In contrast, Afenyi-Annan et al (33) suggested an association between the lack of this receptor and kidney dysfunction.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, Afenyi-Annan et al (33) suggested an association between the lack of this receptor and kidney dysfunction. Based on these observations and on our results showing IL8/RANTES-induced ␣4␤1 clustering on Duffy-positive SRes, we conclude that the presence of DARC, which modulates inflammatory processes, may determine the extent of inflammation in response to hypoxia in SCA.…”
Section: Discussionmentioning
confidence: 96%
“…Provision of Duffy antigen by transfusion may attenuate the inflammatory response associated with ACS by binding chemokines, notably IL-8, via the Duffy antigen receptor for chemokines. 85,86 Duffy antigen is both an inflammatory modulator and the entry portal to the red cell by malarial parasites. 87 The latter role has made Duffy antigen positivity extremely rare in West Africa; approximately 70% of African Americans are Duffy antigen negative.…”
Section: Blood Is Thicker Than Water (Proverb)mentioning
confidence: 99%
“…87 The latter role has made Duffy antigen positivity extremely rare in West Africa; approximately 70% of African Americans are Duffy antigen negative. 86 White patients, who in most U.S. centers constitute the majority of blood donors, generally are positive for FYa and/or FYb, 86 and it is speculated that transfusion of Duffy-positive blood may favorably attenuate the course of ACS by its impact on chemokines. 85 Although no supportive clinical data are yet available, extended cross-matching to exclude Duffy incompatibility may be counterproductive, at least regarding treatment of ACS.…”
Section: Blood Is Thicker Than Water (Proverb)mentioning
confidence: 99%